2000
DOI: 10.1002/1097-0142(20000801)89:3<500::aid-cncr4>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Different risk factors and prognosis for early and late intrahepatic recurrence after resection of hepatocellular carcinoma

Abstract: Early and late intrahepatic recurrences after resection of HCC were associated with different risk factors and prognostic factors. Early recurrences appear to arise mainly from intrahepatic metastases, whereas late recurrences are more likely to be multicentric in origin. The current study suggests that different strategies may be needed for the prevention and management of early and late recurrences. Further studies based on genetic analysis of clonal origins of tumors are required to clarify fully the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
230
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(248 citation statements)
references
References 0 publications
13
230
5
Order By: Relevance
“…As a result, high Snail expression was revealed as an independent risk factor for early recurrence (o1 year). Several reports showed that vp was associated with early recurrence (Fong et al, 1999;Shimada et al, 1999;Poon et al, 2000a). However, in the present study, vp did not correlate with early recurrence.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…As a result, high Snail expression was revealed as an independent risk factor for early recurrence (o1 year). Several reports showed that vp was associated with early recurrence (Fong et al, 1999;Shimada et al, 1999;Poon et al, 2000a). However, in the present study, vp did not correlate with early recurrence.…”
Section: Discussioncontrasting
confidence: 77%
“…Several reports have indicated that early recurrence (o1 year) after hepatic resection arose mainly from im and resulted in a significantly worse prognosis than late recurrence (41 year). Conversely, late recurrence was reported to occur most likely due to MO (Jwo et al, 1992;Poon et al, 2000a;Imamura et al, 2003). Therefore, it is suggested that tumour recurrence in the high Snail expression group is associated with im, which possibly spread through the portal vein invaded by the primary tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence is particularly frequent with HCV-related HCC, and a substantial proportion of recurrence, especially in late phase, is thought to represent de novo, or multicentric, hepatocarcinogenesis [396][397][398]. Therefore, it could be reasonably assumed that antiviral therapy would reduce the overall incidence of recurrence by preventing de novo carcinogenesis.…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 99%
“…Statistically significant differences in risk factors for metastases at different time intervals after definitive treatment have been demonstrated in other cancers, such as gastric and hepatocellular carcinomas. 8,9 Shiraishi et al 8 have demonstrated that, compared with patients who had a late recurrence, patients who had an early recurrence of gastric carcinoma had a significantly increased likelihood of having a larger tumor size at presentation, lymphatic invasion, extensive lymph node metastasis, and more advanced initial stage of disease. In examining hepatocellular carcinoma, multivariate analysis by Poon et al 9 observed that preoperative ''tumor rupture'' and vascular invasion were significant risk factors for early intrahepatic recurrence, whereas cirrhosis was a significant risk factor for late intrahepatic recurrence.…”
mentioning
confidence: 99%